Teknologi Membran Untuk Pengolahan Emulsi Minyak: Review - Farhan Rahmatullah Hikmawan; Evitasari; Geo Aghni Bintang Sukono; Dodi Satriawan (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2020)
In recent years, more and more oily wastewater has been producing from several industrial areas such as the petrochemical plant, the cosmetic plant, the dye plant, even the food plant which has delivered in solemn environmental problems. One of the splittings to surmount this problem is the supply of advanced technology adsorption, such as membrane technology. The separation process with technology was first present in the 21st centenary. The membrane separation process has got a new technology for oily wastewater treatment due to its upper oil excision efficiency and comparatively easy operation. Some of the fittest methods based on the membrane separation process are dehydration of the oil emulsion by evaporation or flocculation followed by microfiltration or by reverse osmosis, membrane distillation, and ultrafiltration. However, the major problem that frequently occurs in the separation process with membrane technology is membrane blockage (membrane fouling). This journal is a review that depicts the latest expansion in membrane technology such as the membrane technology process and the membrane emulsification process. In addition, the influence of operating parameters on membrane performance is discussed in detail.